Coronary microvascular disease assessed by 82Rb-PET-CT is an independent prognostic marker of all-cause mortality. (3rd October 2022) - Hojstrup, S; Hansen, K; Talleruphuus, U; Marner, L; Galatius, S; Rauf, M; Bjerking, L; Jakobsen, L; Christiansen, E; Bouchelouche, K; Prescott, E
Abstract: Background: Coronary microvascular disease (CMD) is a major contributor to e.g. heart failure and angina pectoris, as well as being associated with an increased risk of adverse events. CMD is diagnosed by reduced myocardial blood flow reserve (MBFR), preferably by Positron emission tomography myocardial perfusion CT (PET-CT). Purpose: We aim to determine whether reduced MBFR is associated with an increased hazard of all-cause mortality independently of the extent of perfusion defects in patients suspected of obstructive coronary artery disease. Method: We conducted a multicenter study of all patients referred for 82Rubidium PET-CT imaging between January 2018 and August 2020. Rest and stress examinations were performed using standard imaging protocols. Percentage of perfusion defects were calculated based on summed rest- and difference score. CMD was defined as MBFR ≤2. Patients were followed for all-cause mortality through national registries with no loss to follow-up. Results: Among the 7156 patients studied, 61.8% were men, median age was 69 [61–76 IQR] years, 14.1% had LVEF ≤40%, 58.4% had a previous diagnosis of ischemic heart disease (IHD), 20.1% had atrial fibrillation and 38.9% had MBFR ≤2. A total of 571 (7.8) deaths were observed, more frequently in MBFR ≤2 compared to MBFR >2 (4.2% vs 13.2%, p<0.001). MBFR was significantly associated with reversible hypoperfusion (r 2 =−0.33, p<0.0001). In Kaplan-Meier estimation MBFR ≤2 was significantly associated to all-cause mortality in the overall population as well as in clinically relevant subgroups defined by the extent of reversible and/or irreversible perfusion defects (p<0.05 for all, fig. 1). In multivariate Cox-analysis adjusting for age, sex, Charlson's Co-morbidity index, eGFR, LVEF and LVEF-reserve and stratifying by diabetes, MBFR ≤2 remained a robust predictor of all-cause mortality with a HR 1.73, 95% CI: 1.62–2.19, p<0.0001 (fig. 2). No interaction was found between MBFR and reversible hypoperfusion. In subgroup analysis including only patients with no reversible perfusion defects (n=3095), MBFR ≤2 was still strongly associated with a HR of 2.00, 95% CI: 1.29–3.11, p<0.001 for all-cause mortality. Conclusion: MBFR ≤2 is a robust predictor of all-cause mortality independently of the extent of reversible- and/or irreversible perfusion defects. Information of MBFR should be incorporated in the clinical risk stratification of patients being investigated for ischemia. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Research Committee, Bispebjerg & Frederiksberg University Hospital, scientific scholarship